COMPARATIVE ANALYSIS OF DIFFERENT AGE SCHOOL PUPILS` VIEW ON ONLINE AND TRADITIONAL EDUCATION - Mustafoyeva Irodakhon Ilkhom kizi; Khasanova Yulduz Mukhtor kizi (Bright Mind Publishing, 2025)
This study aimed to investigate the effects of listening to music on students’ learning efficiency and concentration. The study compared students’ learning outcomes with and without music. The effects of music on attention, motivation and task performance were analyzed using questionnaires. The results showed that students who studied in a quiet environment achieved better overall results. They were more effective at understanding text and solving complex problems, suggesting that the absence of music allowed them to better control their thinking processes. While some students noted that music inspired them, the overall results indicated that music was more of a distraction. The genre of music also played an important role. Some students found instrumental music helpful, while others found nature sounds more effective. However, the results of the study showed that studying without music is one of the most reliable ways to increase academic performance. This study emphasizes the importance of considering students' individual learning styles and confirms the superiority of a quiet environment in creating effective learning conditions.
Keywords: Adolescents, learning performance, distract, instrumental music.